Fatigue crack growth analysis of T junction under biaxial compressive–compressive loads. (March 2016) - Shen, Wei; Yan, Renjun; Barltrop, Nigel; Song, Min; Liu, Enqian
Highlights: Carry out biaxial compressive–compressive fatigue test. Analyze the influence of compressive stress on the fatigue life. An equivalent stress intensity factor and crack growth model are proposed. Abstract: The objective of the present research is to analyze systematically the effect of biaxial compressive–compressive stresses on crack growth behavior of T junctions. Pressure structures have many components which are designed to be compressively stressed. This paper describes and summarizes biaxial compressive fatigue crack initiation and propagation characteristics through several T junctions under biaxial fatigue tests. Unlike uniaxial compressive fatigue, multiaxial compressive–compressive fatigue has the intricate characteristics of multi-point crack initiating, short crack group growth behavior and long crack propagating behavior. Moreover, the effective stress intensity factor range K eff and the crack opening threshold K op, max are used to explain the crack growth under biaxial loads instead of the Paris law. Predictions of fatigue crack growth behavior based on the extended McEvily formula agree well with experimental observations.